Aplikasi Pendukung Keputusan dalam Mengukur Tingkat Kepuasan Pelayanan Publik menggunakan Metode MFEP - Pritty Noviana Sari; William Ramdhan; Abdul Karim Syahputra (Universitas Hamzanwadi, 2023)
Services that are said to be excellent are services provided by public service providers, namely the government in an effort to meet the needs of people who receive services and are carried out in accordance with the law. The low quality of services provided to the community certainly has an impact on decreasing public trust in the government. The purpose of this study is to build a decision support system using the Multi Factor Evaluation Process (MFEP) method to measure the level of public service satisfaction in the range sub-district area. In building this system, we apply the waterfall model with stages of analysis, design, implementation, and testing. Analysis is carried out to collect the needs in building this system and analysis using the MFEP method. The criteria used to measure service satisfaction are five criteria, namely certainty of time, comfort, loyalty, responsibility, and task completion. The design of the system we built, consists of use case diagrams and flowcharts. At the implementation stage, a system is made using the web-based MFEP method. Meanwhile, testing on this system uses a black-box to see the functionality of the product. Our findings are in the form of a system that can provide decisions to determine the level of public satisfaction. The results of the analysis showed that the service section was selected as an assessment of the level of public satisfaction with a value of 3,766. In addition, the results of black-box testing show that this system is functioning properly without any errors.